The Effectiveness of the Organic Fertilizer Formula of the PGPR and Biocontrol Agents Consortium on the Growth of Leeks and Reduction of Soft Rot Disease - Bustamam, Hendri; Hartal, Hartal; Wahyuni, Hesti; Gusmara, Herry (KnE Life Sciences, 2022)
The growing demand for organic leeks (Allium fistulosum L.) in the lowlands necessitates the introduction of organic fertilizers and disease-controlling biological agents. Erwinia sp. causes soft rot disease, which results in the loss of 12-40% of the plant’s weight. Because soil-infected pathogens are difficult to control, biological agents that live in the same niche as pathogenic bacteria are used to combat them. This study chose to examine Streptomyces sp. isolate CS1 and Trichoderma viride isolate TTA1 for their potential antagonistic abilities against Erwinia sp. Organic fertilizers and biological agents can be combined in a single-use formulation for maximum efficiency. The study’s primary objective was to see how effective the decomposer microbial consortium’s organic fertilizer formula and biological agents were at promoting leek growth and reducing soft rot disease. The five treatments used in the study were B0 (no pathogen control), B1 (PGPR consortium organic fertilizer = BIOMEG), B2 (BIOMEG + Streptomyces), B3 (BIOMEG + Trichoderma), and B4 (BIOMEG + Streptomyces + Trichoderma). Each experiment was carried out five times. The consortium fertilizer was made in the following manner: the organic matter was fermented for four weeks with a suspension of Bacillus megatrium, Bacillus ap., Pseudomonas sp., and Aspergillus niger, then for two weeks with a suspension of Streptomyces-CS1 and Trichoderma viride-TTA1. The leek seedlings were inoculated with E. caratovora and planted in a 1:4 mixture of consortium fertilizer and soil. The use of biological agents and the PGPR microbial consortium organic fertilizer formula reduced the incidence of soft rot disease in leeks better than the use of the PGPR microbial consortium organic fertilizer formula alone. The organic fertilizer formula of the microbial consortium PGPR + Streptomyces + Trichoderma produced the best results in terms of disease reduction and leek yield. Keywords: Organic-fertilizer, PGPR, Leeks, Softrot-diseases